SPEECH ACTS OF U.K. PRIME MINISTER BORISH JOHNSON’S SPEECH - Risma Ratri Rahayu; Ula Nisa El Fauziah (IKIP Siliwangi, 2021)
Abstract This research was to investigate speech acts of Borish Jonshon’s speech concern in the illocutionary act and the use of speech act analysis by Hymes (2014). The speech was held in Prime Minister’s office and Borish Johnson has used a national TV address at 8.30 p.m. The data of this research taken from the script and speech video of the U.K. Prime Minister named Borish Johnson on 23 March 2020 which talked about Covid-19. The research applied descriptive qualitative as a method and hold in Yule’s speech act theory. Based on the analysis, the researcher was found and analyze 222 utterances. Those are consist of, 36% representative, 33% declarative, 16% directive, 9% expressive, and 6% commissive. As the result was representative is the highest use of the illocutionary aspect found in this research. It can be seen that Borish Johnson hoped that his audiences would follow what he said to reduce the coronavirus disease - 19. Keywords: Pragmatics, Speech Act, Covid-19